I am 'better' than you! The influence of upward social comparison on the intention to work abroad among doctors in Iraq: the mediating mechanism of attitude towards leaving. Issue 11 (17th June 2022) - Mundher Oraibi, Bha-Aldan; Ho, Jo Ann; Raja Yusof, Raja Nerina; Idris, Khairuddin
Abstract: The primary objective of the study was to verify the possibility that social comparisons occurred between professionals (i.e. doctors) in their country of origin to similar others in different hospitals, healthcare systems, and countries. In addition, this study also examined whether these social comparisons resulted in an intention to work abroad among these professionals who remained in their home country. On a sample of 450 Iraqi doctors, we used Structural Equation Modeling through partial least squares (PLS-SEM) to analyse the data. Our study found that upward comparison and attitude towards leaving positively affected the intention to work abroad among doctors who remained in Iraq. Further, the relationship between upward comparison and intention to work abroad was mediated by attitude towards leaving. Our study extends the brain drain literature by examining the role of social comparison, specifically upward comparison, in the migration of professionals and how such a comparison leads to intention to work abroad. The implications for theory and practices to reduce such a comparison among professionals are discussed.